STATUS INFEKSI VIRUS INFLUENZA PADA BEBERAPA SPESIES HEWAN SEBELUM WABAH AVIAN INFLUENZA H5N1 PADA UNGGAS DI INDONESIA - Indrawati Sendow; RM Abdul Adj id; Paul Selleck (BERITA BIOLOGI, 2011)
After outbreak of Avian Influenza HPAI in chicken in mid 2003 in Indonesia, there was a question whether Avian Influenza HPAI was already presence in animals before the outbreak. A retrospective study was conducted to gain information on the presence of Influenza A virus infection in a range of animal species that could be infected by the virus. A total of 1529 animal sera, from 8 species from 12 different provinces which were stored at the Bbalitvet (Research Institute for Veterinary Science) Serum Bank were tested against matrix antigen of Influenza A using the Agar Gel Immunodiffusion (AGID) test. The results indicated that only 0.6% of animal tested which consisted of 4% of duck sera and 0.4% of pig sera were reacted in the AGID test with weak reaction. Those sera were then tested against Influenza A group viruses using an Enzyme Linked Immunosorbent Assay (ELISA), indicated that Influenza A viruses were not detected in either duck and pig positive sera. Those sera which were also tested by HI test against antigens of HI, H3 and H7, also indicated that none of those sera were reacted. In addition, 134 lung of pigs from an abattoir were collected for virus isolation. The viral isolation on chicken embryonated eggs resulted in 12 samples that contained viruses with agglutinated goose and chicken red blood cells. Identification of viruses isolated was done by agglutination test and ELISA. The results showed that none of those isolates were Influenza Type A virus. This study showed that influenza A virus group infection was not detected in animal species sampled before outbreak of AI H5N1 in 2003 in Indonesia.